SEASONAL VARIATION IN BIOMASS AND DISTRIBUTION OF BROWN SEAWEEDS (PHAEOPHYCEAE) IN GULF OF MANNAR, TAMILNADU, INDIA - V. RANI; P. JAWAHAR; R. JEYA SHAKILA (The Bioscan, 2015)
Seasonal variation in the biomass and distribution of brown seaweed (Phaeophyceae) in three locations viz,Valinokkam, Hare Island and Amalinagar of Gulf of Mannar, Tamil Nadu were analysed from August 2012 to July 2013. In total, 21 species of brown seaweeds were recorded, which constituted 14 spp of Sargassum, 2 spp of Padina, 2 spp of Turbinaria and one species each of Spatoglossum, Stoechospermum and Dictyota.At Valinokkam, the maximum number of 16 species was recorded followed by 13 species in Hare Island and 9 species in Amalinagar. Turbinaria, Sargassum acinerium, S. Plagiophyllum and S.swartzii were recorded only at Valinokkam while Spatoglossum asperum and Stoechospermum marginatum were found in the other two locations. The total biomasses of brown seaweeds in the intertidal region were estimated as 26.789kg/m2 in Valinokkam, 16.537kg/m2 in Hare Island and 3.813 kg/m2 in Amalinagar. Based on the diversity estimates like Shannon Wiener index, Margaleaf species Richness and Simpson Evenness, Valinokkam and Hare Island were found to be highly diverse than Amalinagar. Bray-Curtis similarity plot estimation showed about 42-55% of location wise similarities and 45-85% seasonwise similarities in the brown seaweed biomass.